Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran IPAS Melalui penggunaan Media Audio Viasual Kelas IV SDN 01 Duhiadaa Kabupaten Pohuwato - Maryam H Dumako (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
The objective of this study is to enhance students' learning interest in Science and Social Studies (IPAS) by utilizing audio-visual media among fourth-grade students at SDN 01 Duhiadaa, Pohuwato Regency. This study is a Classroom Action Research (CAR) project conducted over two cycles. Each cycle consisted of two meetings and followed four distinct stages: planning, implementation, observation, and reflection. The subjects of this research were 20 students. Data were collected through interviews, observation, documentation, and questionnaires. The results indicated a significant increase in students' interest in the IPAS subject through the use of audio-visual media, with improvements observed in each cycle. In the first cycle, the interest level reached 57%. By the second cycle, students' learning interest significantly improved, with 17 students (85%) meeting the criteria for success. Based on these findings, it can be concluded that the learning interest of fourth-grade students at SDN 01 Duhiadaa was successfully improved through the application of audio-visual media.